Salivary, gingival crevicular fluid and serum levels of ghrelin and chemerin in patients with periodontitis and overweight. (20th June 2017) - Jentsch, H. F. R.; Arnold, N.; Richter, V.; Deschner, J.; Kantyka, T.; Eick, S.
Abstract : Background and Objective: Nutrition and body weight are modifying factors for periodontitis. The purpose of this study was to quantify two molecules (ghrelin and chemerin), released in association with food intake and obesity, in periodontally healthy and diseased individuals with respect to different body mass categories. Material and Methods: The two main groups (patients with chronic periodontitis and periodontally healthy/gingivitis volunteers) were subdivided into groups of subjects with normal weight [body mass index (BMI) <25] and groups of overweight/obese subjects (BMI ≥25). Subgingival bacteria were analysed and the levels of acylated and total ghrelin, chemerin and interleukin‐1β (IL‐1β) were assessed in saliva, gingival crevicular fluid and serum. Results: The amount of Treponema denticola present subgingivally was significantly higher in the groups of patients with chronic periodontitis as well as in periodontally healthy/gingivitis individuals with BMI ≥25 than in periodontally healthy/gingivitis individuals with BMI <25. The amount of total ghrelin in gingival crevicular fluid differed significantly between the groups, with the lowest levels found in the group of patients with chronic periodontitis and BMI ≥25. The levels of chemerin in gingival crevicular fluid were significantly higher in each chronic periodontitis group than in periodontally healthy/gingivitis individuals with BMI <25. However, the level of IL‐1β in the gingival crevicular fluid was most differentiating between the groups, with the highest levels found in the group of patients with chronic periodontitis and BMI <25 and the lowest levels in periodontally healthy/gingivitis individuals with BMI <25. No significant differences between any groups were seen for chemerin or for acylated ghrelin in the stimulated whole saliva, or for acylated and total ghrelin in peripheral blood serum. The BMI correlated with the serum level of chemerin. Conclusion: Low ghrelin and high chemerin levels in the gingival crevicular fluid might be linked to periodontal disease and overweight/obesity. However, unlike IL‐1β, the levels of chemerin and ghrelin in gingival crevicular fluid are not reliable indicators of periodontal destruction.